Time irreversibility of heart rate oscillations in newborns – Does it reflect system nonlinearity?. (May 2015) - Czippelova, B.; Chladekova, L.; Uhrikova, Z.; Javorka, K.; Zibolen, M.; Javorka, M.
Highlights: Time irreversibility is present in newborn's heart rate oscillations. Surrogate data analysis revealed heart rate control system nonlinearity. Irreversibility index P % detects sympathetic dominance in newborns. Abstract: The aim of our research was to find out if the time irreversibility as a sign of specific class of nonlinear dynamics is present even in the newborn's heart rate oscillations. Multiscale irreversibility indices (Porta's index P %, Guzik index G % and Ehlers index E ) of the heart rate signals were computed in 20 healthy neonates. The presence of system nonlinearity was assessed by surrogate data analysis. The results of our analysis revealed asymmetrical nature of heart rate oscillations present in the majority of neonatal heart rate recordings. Moreover, time irreversibility index P % was able to detect shift of sympathovagal balance toward sympathetic dominance in newborns. Our findings support the concept of nonlinearity as a universal feature of the biological control system even in the early stage of the system maturation. This finding supports the application of nonlinear methods to heart rate variability analysis.